PENGARUH JENIS FIKSATOR TERHADAP PENCELUPAN KAIN SUTERA DENGAN MENGGUNAKAN LIMBAH STERILIZER PRODUKSI CRUDE PALM OIL (CPO) - Dewi, Hartami; Ichwan, Muhammad; Salis, Witri Aini; Saputra, Andri (JURNAL RISET INDRAGIRI, 2023)
Natural dyes are used as a non-biodegradable alternative to synthetic dyes. Fresh palm fruit bunches (FFB) are known to contain several compounds which are thought to be used as alternative natural dyes, such as: flavonoids, caratenoids and tannins. Apart from that, the use of industrial waste is an added value in this research. Fixation is the most important stage after the color dyeing process because fixation is a stage to lock and strengthen the direction of the color. The types of fixator used in this research were tawas, kapur, and tunjung. The aim of this research is to see whether CPO production sterilizer waste can be used as an alternative to natural dyes and how the type of fixator affects the dyeing results of silk fabric. The evaluation parameters of the dyeing results observed were the value of color maturity, color evenness, and washing and rubbing fastness. The results showed that the three types of fixator had an effect on the color aging value produced but did not have a significant effect on the fastness of washing and scrubbing. The highest K/S value was found in Tunjung mordant at 1.33 at ʎmax 400nm. Meanwhile for Kapur and Tawas mordant it is 0.72 and 0.71. Keywords: fixator, natural dyes, waste